The triple bottom line effect on emerging market companies: A test of corporate social responsibility and firm value relationship - Arafat, M. Yasser; Warokka, Ari; Abdullah, Haim Hilman; Septian, Rosa Rachmat (IBIMA Publishing, 2012)
Over the last twenty years, after corporations have historically focused their reporting systems on the provision of financial information needed by managers and shareholders to assess risks and calculate returns, the global awareness of the need to assess the full spectrum of corporate value has grown dramatically.The triple bottom line or total returns on capital—economic, social, or environmental—are now tracked with increasing regularity. Prior research has revealed that a significant pressure of economic changes, an increase in interest in corporate social responsibility (CSR) in recent years, and an acknowledgement of it as an important research topic has brought a bigger and wider effort to build a comprehensive framework.Little empirical research on the effect of corporate social responsibility together with profitability on firm value is done in Southeast Asian countries. This study extends the literature that has been done mostly in western societies by proposing a further linkage between social responsibility, profitability, and firm value, which is rarely investigated in non-western societies.The study analyzed 35 Indonesian manufacturing firms that are listed in Indonesian Stock Exchange (IDX) and report their CSR as the supplement in the annual report.Statistic methods used for testing the hypothesis are T-test and multivariate regression model.The empirical results reveal that CSR has significantly influenced the firm value of Indonesian manufacturing companies.However, one striking finding in this study is the insignificant influence of two measures of profitability, i.e. ROA and ROE, over firm value of those companies have good CSR.These results explicitly show how firms in emerging countries are going to be more concerned with social sustainability and long-run profitability.